Malondialdehyde (MDA) and 8-hydroxy-2′-deoxyguanosine (8-OHdG) in ischemic stroke: a systematic review - Dodik Tugasworo; Awal Prasetyo; Aditya Kurnianto; Retnaningsih Retnaningsih; Yovita Andhitara; Rahmi Ardhini; Jethro Budiman (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2023)
Abstract Introduction The low blood flow in ischemic stroke reduces oxygen and glucose and induces a series of reactions that produce free radicals. Free radicals can destroy cell membranes (lipid peroxidation) marked by the elevation of malondialdehyde (MDA), and the damage of deoxyribonucleic acid (DNA) showed by the elevation of 8-hydroxy-2’-deoxyguanosine (8-OHdG). This review aimed to assess and conclude the research-based study systematically to analyze the relationship of MDA/8-OHdG and ischemic stroke. Method Cochrane handbook for systematic reviews, the guideline of preferred reporting items for systematic review and meta-analysis (PRISMA), and synthesis without meta-analysis (SWiM) in systematic reviews: reporting guideline was used as guideline in this systematic review. Inclusion criteria in this review were primary studies of every design, articles published in English around January 2000–December 2021, and the study used human as subject. A systematic literature search was applied in 15 electronic medical journals. The authors assessed the study quality and risk of bias of each included study. Results The authors evaluated 374 studies found in literature searching, 30 studies met the criteria for this review, and then underwent the assessment of study quality and risk of bias. Conclusion MDA has the role as oxidative stress biomarker, outcome predictor, mortality predictor, post-stroke cognitive impairment predictor, post-stroke depression predictor, and hand grip strength predictor of ischemic stroke; while 8-OHdG has the role as oxidative stress biomarker, outcome predictor, mortality predictor, post-stroke cognitive impairment predictor, post-stroke depression predictor of ischemic stroke.